Boundary Segmentation and Detection of Diabetic Retinopathy (DR) in Fundus Image - Nor Rul Hasma, Abdullah; M. F. S., Nasarudin; M., Mustafa; Pebrianti, Dwi; Rosdiyana, Samad (2015)
Recently, the automatic detection system or Computer-Aided Detection (CAD) is widely developed in the medical field to screen or diagnose the medical image. This paper presents the boundary segmentation and detection of Diabetic Retinopathy (DR) in fundus image. The proposed method uses Fuzzy C-Means for clustering and detect the boundary of the DR object. The number of cluster used in this work is 3 and the average number of iterations is 28.The DR region is successfully detected by FCM and the average processing time is 1.235s.